2012
DOI: 10.1055/s-0032-1315261
|View full text |Cite
|
Sign up to set email alerts
|

From Tyrian Purple to Kinase Modulators: Naturally Halogenated Indirubins and Synthetic Analogues

Abstract: Indirubin l " indigo l " Tyrian purple l " Hexaplex trunculus l " Bolinus brandaris l " Muricidae l " protein kinases l " CDKs l " GSK-3β l " stem cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 168 publications
(219 reference statements)
0
29
0
Order By: Relevance
“…These include the CDK family members CDK1, CDK2, and CDK5, in addition to PDK1, JAK/STAT3, and GSK-3a/b. 22,26,40,[43][44][45] GSK-3a/b is a ubiquitously expressed serine-threonine kinase encoded by distinct genes. 47 The two isoforms share 97% sequence homology within their catalytic domains but differ in their C and N termini.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the CDK family members CDK1, CDK2, and CDK5, in addition to PDK1, JAK/STAT3, and GSK-3a/b. 22,26,40,[43][44][45] GSK-3a/b is a ubiquitously expressed serine-threonine kinase encoded by distinct genes. 47 The two isoforms share 97% sequence homology within their catalytic domains but differ in their C and N termini.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the inhibition of GSK-3b activity by 6BIO. 40 GSK-3b is known to phosphorylate the b-catenin protein and to enhance its degradation. 41 Blocking the activity of GSK-3b will thus elevate levels of b-catenin.…”
Section: Figure 2 6bio Enhances Mir21-aso Function In Tumor Microsphmentioning
confidence: 99%
See 1 more Smart Citation
“…Although kinase inhibitors have been discovered from various sources [12][13][14][15], the major obstacle to kinase-directed drugs is the cross-inhibition linked to their highly homologous ATPbinding sites [12]. Staurosporine, although too toxic for clinical use, is a potent inhibitor of PhK (Ki = 0.37 nM) [5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of indirubin derivatives have been synthesized and characterized with respect to kinase inhibition and anticancer properties. [5][6][7][8][9][10][11] We reported that 5 0 -methoxyindirubin, but not by indirubin itself, was highly cytotoxic against neuroblastoma cells in comparison with normal cells, human umbilical vein endothelial cells (HUVEC) and normal human dermal fibroblasts (NHDF). 12 More recently, we determined that three of these derivatives, 5-methoxyindirubin, indirubin 3 0 -oxime and 7-methoxyindirubin 3 0 -oxime, suppressed multi-drug resistant gene 1 (MDR1) expression by interaction with a transcription factor, NF-Y, in a tumor cell-type specific manner.…”
mentioning
confidence: 99%